KETAHANAN HIDUP PASIEN GAGAL GINJAL DENGAN METODE KAPLAN MEIER (Studi Kasus di Rumah Sakit Umum Daerah dr. R. Soedjati Soemodiarjo Purwodadi) - Immawati Ainun Habibah; Tatik Widiharih; Suparti Suparti (Jurnal Gaussian, 2018)
Chronic Kidney Disease (CKD) is a failure of kidney function that which get slowly and can not recover. Most of the patients CKD get death sudden becuse of cardiovascular complications (related to the heart and blood vessels) however only minor part can reach terminal phase (CKD stage 5) which need replacement therapy of Kidney. Replacement therapy of Kidney are hemodialysis, peritoneal dialysis, and Kidney transplant. Because of that, the importance to study how long the patient opportunity is life endurance analysis.  Survival analysis methods to life depend from the life time and status of individual life time. Survival analysis uses Kaplan-Meier method. During the observation process, there is different observations so censor type III is choosen. Censor type III is censoring type which research is done to individual in and out for determine time, because of that estimation value of survival can be caunted using Kaplan Meier method with censor type III. This research uses medical records data from the patients with kidney failure period 1 January 2014 until 30 November 2017 in RSUD dr.R. Soedjati Soemodiarjo Purwodadi Grobogan Regency. The results of the analysis and discussion are known that if hemodialysis getting longer done, estimation value of survival. With an average estimate of survival is 776 days. Keywords: Chronic Kidney Disease, Survival Analysis, Kaplan Meier